"Med prakso sem spoznal, da sem študij dobro izbral" - evalvacija pedagoške prakse prve generacije študentov bolonjskega študija francoščine - Lah, Meta (Vestnik za tuje jezike, 2015)
The paper analyzes the teaching practice of the first generation of students of French language at the Faculty of Arts (University of Ljubljana). The instruments used are two parts of the students' portfolio - the questionnaire for students and the final reflection. In the academic year 2014/15 the teaching practice was performed by all 12 students. The analysis of the questionnaires and the reflections shows that they were mostly satisfied with the practice. Nevertheless, the analysis also showed some shortcomings, which we will try to correct in the future. The author also draws attention to some problems at the system level.
Keywords: francoščina; French; pedagoška praksa; učitelji; Slovenia; Slovenija; vprašalniki